Prevalence and risk markers of early psychological distress after ICD implantation in the European REMOTE-CIED study cohort. (1st August 2017) - Versteeg, Henneke; Timmermans, Ivy; Meine, Mathias; Zitron, Edgar; Mabo, Philippe; Denollet, Johan
Abstract: Background: Evidence on psychological distress in patients living with an implantable cardioverter defibrillator (ICD) is inconclusive. The current study is the first to examine the prevalence and risk markers of anxiety and/or depression in a large international cohort of European ICD patients with or without cardiac resynchronization therapy (CRT). Method: Heart failure patients (N = 569) from France, Germany, Spain, Switzerland and the Netherlands participating in the REMOTE-CIED study completed a set of questionnaires 1–2 weeks post ICD-implantation, including the 7-item Generalized Anxiety Disorder scale and the 9-item Patient Health Questionnaire to assess anxiety and depressive symptoms, respectively. Patients' clinical data were obtained from their medical records. Results: The prevalence of anxiety was 16% and that of depression 19%, with 25% of patients reporting one or both types of distress. Multivariable logistic regression analysis showed that age < 60 years (odds ratio (OR) = 2.5[95% confidence interval = 1.2–5.0]), having a threatening view of heart failure (OR = 4.7[2.7–8.2]), a high level of ICD-related concerns (OR = 2.9[1.7–5.1]), Type D personality (OR = 2.4[1.3–4.4]), poor patient-reported health status (OR = 2.2[1.3–3.9]) and receiving psychotropic medication (OR = 3.0[1.5–5.9]) were positively associated with distress, while attending cardiac rehabilitation (OR = 0.3[0.2–0.7]) was negatively associated with distress. Conclusions: A significant subset of European ICD and CRT-defibrillator patients reports anxiety and/or depression in the first weeks post implantation. Patients' psychological characteristics, especially negative perceptions about their illness and treatment, were the strongest associates of distress. Timely identification of these patients is essential as they may benefit from psychological interventions and cardiac rehabilitation in terms of improved quality of life and prognosis.